Optical microscopy study on the marginal adaptation of tunnel restaurations with resins composite - Cornelia Bîcleşanu; Anamaria Florescu; Alexandru Burcea; Ştefan Manea; Tiberiu Botea (Amaltea Medical Publishing House, 2019)
Minimally invasive restoration is the modern way of treatment in dental therapy. Tunnelling / tunnel preparation is a viable option for minimally invasive restoration of proximal caries located on the posterior teeth, with approach from the occlusal aspect of the tooth. The aim of this study is to check by means of optical microscopy the ability of marginal adaptation to dental structures of the tunnel type restorations. Material and method. For this study, 36 extracted teeth were used, on which tunnel preparations were performed both on the mesial and the distal aspects of the teeth. The preparations took into account the protocol and principles of minimally invasive therapy. For all restorations, a combination of composite resins was used. The tunnel preparation was restored using flow composites and a normal consistency composite was used to restore occlusal morphology. Depending on the restoration materials and the adhesive system used, the teeth were divided into 3 groups with 12 teeth each. Group 1: Fine Etch 37%, Adper Single Bond 2, 3M Espe, Beautifil Flow Plus, Shofu, Beautifil II, Shofu. Group 2: Fine Etch 37%, Zmack Bond, Zhermack, Es Flow, Zmack Comp, Zhermack. Group 3: Opti Bond XTR, Kerr, SDR, Dentsply, Premise, Kerr. To highlight marginal microleakage, the teeth were isolated using a nail polish applied across the entire dental surface except for the 2 mm area surrounding the proximal restorations. They were then immersed for 24 hours in 2% methylene blue. Finally, the teeth were washed and cut in mesio-distal direction at low speed by means of a diamond disk, under cooling with water. Results and discussions. The optical microscope examination revealed marginal microleakage in all three restored groups. The results of the study showed that the lowest microleakage was revealed in restorations that used giomers and single-step adhesive system. Conclusions. The combination of flow and high-consistency composite resins seems to be a viable solution for tunnelling restorations.